What harmonised and registered unemployment rates do not tell - Regina Konle-Seidl; Britta Lüdeke (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
The most commonly used statistical sources for the analysis of unemployment are registered unemployment (RU) at the national level and internationally harmonised unemployment data provided by the European Labour Force Survey (EU-LFS) according to the International Labour Organisation (ILO) standard. The logic behind both unemployment statistics is to count people "without work" only when they are "actively looking" and "available for work". This logic does not coincide necessarily with the understanding of unemployment in the general public. That's why governments and Public Employment Services (PES) are often blamed to "hide" unemployed individuals participating in active labour market measures or being temporarily ill. Our methodological study provides an in-depth analysis of the discrepancies between registered unemployment (RU) and internationally harmonised unemployment (LFSU) in a comparative view. For ten selected EU-countries (Austria, Finland, France, Germany, Ireland, Netherlands, Poland, Spain, Sweden and the UK) we show in which countries the registers are more restrictive than the survey and vice versa. We then identify the populations groups which help to understand the discrepancies between both figures in most countries (young and older people, marginally employed, participants in active labour market programmes) and extend the view to additional indicators of non-employment. Finally, we explore differences in the calculation of the length of individual unemployment spells between both data sources and show that neither register based national nor survey based international statistics adequately reflect the long-term exclusion from regular, genuinely market-based employment. – – Zur Messung der Arbeitslosigkeit werden überwiegend zwei statistische Quellen herangezogen: die registrierte, auf administrativen Daten basierende Arbeitslosigkeit (RU) sowie die international gemessene Erwerbslosigkeit (LFS-U), die auf Selbstauskunft in der Europäische Arbeitskräfteerhebung basiert. Letzterer liegt eine einheitliche Definition von Erwerbstätigkeit und Erwerbslosigkeit in der Arbeitskräfteerhebung (Labour Force Survey, kurz EU-LFS) aller europäischen Länder zugrunde. Die Logik hinter beiden Arbeitslosenstatistiken ist, Menschen 'ohne Arbeit' nur dann als arbeitslos bzw. erwerbslos zu zählen, wenn sie 'aktiv suchen' und tatsächlich auch dem Arbeitsmarkt 'zur Verfügung stehen'. Diese Logik stimmt nicht notwendigerweise mit dem öffentlichen Verständnis von Arbeitslosigkeit überein. In der Öffentlichkeit ist deshalb oft von Statistiktricks und 'versteckten Arbeitslosen' die Rede. In diesem methodischen Beitrag untersuchen wir komparativ Unterschiede im Verhältnis von national gemessener und international harmonisierter Arbeitslosigkeit in zehn EU-Staaten: Österreich, Finnland, Frankreich, Deutschland, Irland, Niederlande, Polen, Spanien, Schweden und Großbritannien. Wir zeigen, in welchen Ländern die Registerdaten restriktiver sind als die Befragungsdaten und umgekehrt. Wir identifizieren Bevölkerungsgruppen, die im Wesentlichen für die Diskrepanzen in beiden Statistiken verantwortlich sind (junge und ältere Personen, geringfügig Beschäftigte, Teilnehmer an arbeitsmarktpolitischen Maßnahmen) sowie Personen, die nicht als arbeitslos/erwerbslos sondern als inaktiv eingestuft werden. In einem weiteren Schritt widmen wir uns der Berechnungsweise der Dauer von Arbeitslosigkeit (Langzeitarbeitslosigkeit und chronische Arbeitslosigkeit) und zeigen, dass weder nationale Arbeitslosenstatistiken noch die internationale Erwerbslosenstatistik den langfristigen Ausschluss von regulärer Beschäftigung angemessen wiedergeben.
Keywords: 330